Menanamkan karakter abad 21 untuk siswa SMA - Muhammad Hasan; Sri Astuty; Andi Tenri Ampa (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The Community Partnership Program (PKM) partners are Makassar Hang Tuah High School Students. The problem is:(1) students still consider violent behavior as natural, (2) there is no understanding of students about the negative effects ofviolent behavior, and (3) the role of parents and teachers is not optimal in instilling good behavior and character towardsstudents. External targets are (1) the reduction in violent behavior that occurs among students, and (2) the creation of a conduciveatmosphere in schools, so that it can support the implementation of quality learning activities. The methods used are: lectures,discussions, and questions answer. The results achieved are (1) students understand the negative impact of violent behavior inschools and in the environment, (2) students understand the importance of good character to support their future, (3) students canunderstand the importance of the role of parents in anticipating behavior violence that occurs to students, and (4) studentsincreasingly understand the character of the 21st Century.